Anti-PD-1 induced collagenous colitis in metastatic melanoma: a rare severe adverse event. Issue 6 (December 2020) - Janela-Lapert, Raphaël; Bouteiller, Julie; Deschamps-Huvier, Aurélie; Duval-Modeste, Anne-Bénédicte; Joly, Pascal
Abstract : Immunotherapy has improved the overall survival of patients with metastatic melanoma. Inflammatory bowel disease-like colitis is the most frequent gastrointestinal serious adverse event in patients treated with immune-checkpoint inhibitors. Collagenous colitis is microscopic colitis. Only two cases of immune-checkpoint inhibitors induced collagenous colitis have been reported. A man in his early 70s was referred for a metastatic melanoma treated with nivolumab as the fourth line of treatment. During the 21st cycle, the patient complained of watery, nonbloody diarrhea (around six times per day). Rectosigmoidoscopy showed no mucosal lesion. A thickened subepithelial collagen band was evidenced by trichrome staining, which was suggestive of collagenous colitis. Nivolumab was stopped and the patient was treated with budesonide 9 mg/day in combination with loperamide and cholestyramine, leading to improvement of diarrhea. However, worsening of digestive symptoms during tapering of corticosteroid dose required the permanent discontinuation of nivolumab. Due to the very low number of cases reported to date and their different evolution under corticosteroids, it is not clear whether or not immune checkpoint inhibitors can be restarted in these patients.